Early Modern English Borders: Homogeneity and Heterogeneity. (15th August 2022) - Chen, Boyi
Abstract : This article discusses the process of English border-formation in Wales, Ireland, Scotland and around the Channel Islands, including efforts of the English government in border formation, and the local identities of borderlands. I evaluate political considerations, as well as examining social and cultural resonances to show that the English historical border was formed as part of the consolidation of state and nation in terms of Wales, Scotland, Ireland and the Channel Islands. I argue that border 'building' was not always smooth, or to be taken for granted in terms of state-building. The borderlands of the English state have manifested both a homogeneity and heterogeneity in the four regions, each with four particular forms or tendencies in their deep structures: homogeneity, from homogeneity to heterogeneity, from heterogeneity to homogeneity, and heterogeneity. In the article, I use homogeneity to refer to the status of the acculturational tendency, while using heterogeneity to refer to a deviation of the interaction between the English state and other states or nations. This article touches upon a topic not restricted to the British case, but relevant worldwide: the construction of borders in the context of the fundamental conflict between a 'nation', which is to say a culturally and often linguistically distinctive entity, and a 'state'.